INSURANCE OBLIGATIONS IN THE CIVIL LAW OF THE REPUBLIC OF UZBEKISTAN: THEORETICAL AND COMPARATIVE ANALYSIS - Satvaldieva Yulduzkhon Khatamzhan kizi; Zhololidinova Dilara Zovki kizi (Western European Studies, 2025)
This article presents a comprehensive legal analysis of insurance obligations in the civil law of the Republic of Uzbekistan. It examines the concept and types of insurance, key characteristics of property and personal insurance contracts, and the procedures for their conclusion, execution, and termination. Special attention is given to the legal nature of compulsory insurance, its role in protecting the property interests of individuals and legal entities, and its influence on financial stability and insurance market development. The paper highlights current regulatory issues, including insurable interest, liability of parties, double and mutual insurance. A comparative legal analysis of insurance regulation in Russia, Germany, the USA, and Kazakhstan is conducted, revealing both universal approaches and national specifics. The author concludes that Uzbekistan’s insurance legislation is generally in line with international standards, though certain provisions require further improvement.
Keywords: insurance; insurance obligation; civil law; property insurance